If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 3(x + -2) = 0 Reorder the terms: 12x + 3(-2 + x) = 0 12x + (-2 * 3 + x * 3) = 0 12x + (-6 + 3x) = 0 Reorder the terms: -6 + 12x + 3x = 0 Combine like terms: 12x + 3x = 15x -6 + 15x = 0 Solving -6 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 15x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 15x = 0 + 6 15x = 0 + 6 Combine like terms: 0 + 6 = 6 15x = 6 Divide each side by '15'. x = 0.4 Simplifying x = 0.4
| 10=x^2-3x | | 3(x+6)=11x-2 | | 6p-p(p-1)=0 | | 5x+18=10x-1 | | 8n+21=-43 | | t(3t+1)= | | 2x^2+10x=-2 | | 3x=5x+4 | | h+9=-3h-7 | | 8x^4-4x^3-2x-1=0 | | h+9=3h-7 | | 6m^2-7m-5= | | 5u^2+24u-5= | | -3(3y-6)-y=-3(y-2) | | 17x+9=4(4x+8) | | x^4y^2+7x^2y+5= | | -2x=-8 | | 3(X+6)=4(2X-8) | | 8z^2+32-az-4a= | | y=17.5(2)+19 | | x^4-81= | | 6x^2+2x= | | 12c^2+36ct+27t^2= | | 40v^4+50v^3b-35v^2b^2= | | 9b^2-3b-24=0 | | 8x-7=3x+10 | | 50-2y^2=0 | | 40v^4+30v^3b-25v^2b^2= | | y=4x^2+8x-6 | | 18x^3+51x^2-42x= | | 6b^2-34b-112=0 | | 2=2-14 |